2002
DOI: 10.1128/jcm.40.3.863-867.2002
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Sensitive Detection of Physical Status of Human Papillomavirus Type 16 DNA by Quantitative Real-Time PCR

Abstract: A rapid quantitative real-time PCR method was employed to quantify the copy number of E2 and E6 genes for analysis of the physical status of human papillomavirus type 16 (HPV-16) DNA. Significant differences with respect to both copy numbers were found when more than 40% of HPV-16 DNA was integrated with disruption of the E2 gene in an experimental model. The physical status of HPV-16 DNA in 50 clinical samples was exclusively episomal in 21 cases (42%), concomitant in 14 cases (28%), and integrated in 15 case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
66
1
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(77 citation statements)
references
References 23 publications
8
66
1
2
Order By: Relevance
“…In contrast to advanced lesions and cervical cancer (36), integration of HPV DNA into the host genome has been considered a rare event in early preneoplastic lesions of the cervix. Recent studies that used novel quantitative real-time PCR techniques, however, have demonstrated that integration of HPV may occur in early CIN lesions (37) and even in those containing HPV but no CIN (38). Also, rapid progression, in 1 to 2 years, from non-CIN lesions or CIN 2 to CIN 3 was shown to be associated with a heavy load of integrated HPV.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to advanced lesions and cervical cancer (36), integration of HPV DNA into the host genome has been considered a rare event in early preneoplastic lesions of the cervix. Recent studies that used novel quantitative real-time PCR techniques, however, have demonstrated that integration of HPV may occur in early CIN lesions (37) and even in those containing HPV but no CIN (38). Also, rapid progression, in 1 to 2 years, from non-CIN lesions or CIN 2 to CIN 3 was shown to be associated with a heavy load of integrated HPV.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the use of these consensus primers may leave some important oncogenic HPV types undetected because of loss of the L1 sequence during viral integration. In clinical practice this can be critical, since integrated HPV 16/18 DNA has been revealed in various stages of dysplasia (Nagao et al, 2002;Gallo et al, 2003) and is shown to be common in patients with cervical carcinomas (Park et al, 1997;Kalantari et al, 1998;Walboomers et al, 1999). Therefore, the use of type-specific PCR, directed against one of the early-region genes (preferentially E6 and E7), is always recommended.…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies using real-time PCR (Nagao et al, 2002;Peitsaro et al, 2002), the integration of the genome of high-risk HPVs was detected not only in cervical carcinomas but also in CINs. Peitsaro et al (2002) showed that 14 of 15 HPV-16 -positive CIN1/2s contained HPV-16 DNA in either integrated or mixed form.…”
Section: Discussionmentioning
confidence: 99%
“…An earlier study using 2-dimensional gel electrophoresis showed that integration of high-risk HPV was characteristic of cervical carcinoma but not of CIN (Das et al, 1992). However, recent studies using real-time PCR suggested that integration of high-risk HPV into the host genome occurs in a fraction of cases of CIN (Nagao et al, 2002;Peitsaro et al, 2002). The factors that influence the HPV-mediated progression of dys-plastic lesions to invasive carcinoma have not been determined.…”
mentioning
confidence: 97%